MEASUREMENT OF ELASTICS, VISCOPLASTICS AND FIRMNESS PROPERTIES OF WHEATS STEMS - DUNCA, Juraj; DUNCOVÁ, Alena; Ondrej, ŠVEC (Trends in education, 2008)
In this work are examined elastics, viseoplastics and firmness properties of wheato stems.